The Roles of TRAF3 in Immune Responses. (16th February 2023) - Lin, Mengjiao; Ji, Xiaoli; Lv, Yan; Cui, Dawei; Xie, Jue
Abstract : Seven tumor necrosis factor receptor- (TNFR-) associated factors (TRAFs) have been found in mammals, which are primarily involved in the signal translation of the TNFR superfamily, the Toll-like receptor (TLR) family, and the retinoic acid-inducible gene I- (RIG-I-) like receptor (RLR) family. TRAF3 is one of the most diverse members of the TRAF family. It can positively regulate type I interferon production while negatively regulating signaling pathways of classical nuclear factor- κ B, nonclassical nuclear factor- κ B, and mitogen-activated protein kinase (MAPK). This review summarizes the roles of TRAF3 signaling and the related immune receptors (e.g., TLRs) in several preclinical and clinical diseases and focuses on the roles of TRAF3 in immune responses, the regulatory mechanisms, and its role in disease.